Diagnosis of Acute Appendicitis: Ultrasound as First-Line Imaging Modality: Diagnosis of Acute Appendicitis - Chaudhary, Waiz; Ahsan, Muhammad Adnan; Hashim, Muhammad; Ather Azeem Shams, Rana Muhammad; Haider, Muhammad Arslan; Zahra, Syeda Iman; Zahid, Warda; Kazmi, Fizza; Arshad, Zainab; Zainab, Anosh (Pakistan Journal of Health Sciences, 2022)
The most prevalent abdominal emergency is acute appendicitis. Atypical manifestations may lead to diagnostic uncertainty and a delay in therapy, even if the clinical diagnosis may be simple in patients who exhibit conventional signs and symptoms. When laboratory results are presented, they often show a left shift and an increased leukocytosis. The chance of increased C-reactive protein measurement is high. Imaging modalities have become extremely important in the diagnostic work-up of patients with suspected acute appendicitis in order to maintain the low rate of negative appendectomy because the clinical diagnosis of acute appendicitis continues to pose a challenge to emergency physicians and surgeons. Ultrasound, computed tomography and magnetic resonance imaging modalities are used in diagnosis but we feel that all patients with suspected appendicitis should get an ultrasound. Because ultrasound has outstanding specificity, readily available, no ionizing radiation and cost is low.